Pelatihan Terapi Bermain Peran Dengan Kearifan Budaya Batobo Dalam Peningkatkan Perkembangan Sosial Emosional pada Anak Usia Dini di Kabupaten Kampar - Amalia, Rizki; Sa’idah, Amin Yusi Nur; Alim, Melvi Lesmana (Institut Teknologi Pendidikan Indonesia, 2024)
This community service activity aims to 1) Provide an understanding of social-emotional problems in early childhood, 2) Provide role-play therapy training using the wisdom of Batobo Culture in improving social-emotional development in early childhood. The problem faced by partners is that teachers experience difficulties in dealing with students' social emotional problems. The organizers of guidance and counseling in PAUD are the PAUD teachers themselves, for this reason, with role-play therapy training with the wisdom of Batobo Culture, it helps PAUD teachers in dealing with the problems of PAUD children. The aim of role-playing therapy with the wisdom of Batobo Culture is to deal with social-emotional problems in early childhood. The method used is 1) planning 2) implementation stage in the form of presentation, discussion and practice, 3). Evaluation of activities.